Implementasi pembelajaran agama Islam berbasis teknologi digital untuk menghadapi tantangan masyarakat 5.0 - Hakim, Arif Rahman; Masumah, Nurzakiyah Al (Al-Liqo: Jurnal Pendidikan Islam, 2025)
The rapid development of technology presents challenges for various sectors, including Islamic religious education, to adapt to the digital era of Society 5.0. This research aims to analyze the implementation of digital technology-based Islamic religious learning and the challenges faced in the process. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. The results of the study indicate that digital technology has the potential to enrich the learning experience, increase accessibility, and provide interactive learning methods. The main challenges found include limited infrastructure and low technological skills among educators. This study recommends improving infrastructure, providing technology training for teachers, and integrating the Islamic religious education curriculum with digital technology. Digital technology-based learning has the potential to enrich students' learning experiences and increase their understanding of Islamic religious teachings in the face of the challenges of Society 5.0.